Monitoring of singlet fission via two-dimensional photon-echo and transient-absorption spectroscopy : simulations by multiple Davydov trial states - Sun, Kewei (2020)
Employing the Dirac-Frenkel time dependent variational method, the nonlinear spectra monitoring the singlet fission process mediated by a conical intersection (CI) of the two lowest excited electronic states are investigated for different optical dephasings. The simulated two-dimensional spectra at different population times follow ultrafast population transfer through the CI and exhibit spectral features related to the tuning mode. The anticorrelated oscillations of cross peaks located at symmetric positions with respect to the main diagonal are clearly identified after the stimulated-emission contribution quenches. The simulated transient absorption signals show a fast decay of the first excited singlet state and exhibit multiple peaks revealing the tuning mode. These findings could be regarded as signatures of the CI in the singlet fission process.